Escape of the fiddler crab Uca rapax (Smith, 1870) (Crustacea: Ocypodidae) in the state of Minas Gerais, Brazil - Magalhães, André Lincoln B.; Costa, Tânia Marcia [UNESP] (My University, 2007)
A escape of the fiddler crab Uca rapax (Smith, 1870), in the state of Minas Gerais is reported for the first time. This record was made more than 200 km away from its original habitat, a mangrove area in the state of Rio de Janeiro. The species has been introduced in ponds in the study area, located in the largest ornamental pisciculture/aquaculture center of Brazil. Male individuals of U. rapax were observed engaged in territorial and courtship displays around their burrows. Despite this, there is no well-established population of the species in the area, due to the physiological dependence of the larvae on brackish water. © 2007 Instituto de Ciências Biológicas - UFMG.
Keywords: Brazil; Escape of exotic organisms; Fiddler crab; Minas Gerais; Uca rapax; aquaculture; crab; escape behavior; introduced species; mangrove; Rio de Janeiro [Brazil]; South America; Crustacea; Decapoda (Crustacea); Ocypodidae